Performance Effectiveness of Civil Servants Police Unit in Controlling Street Vendors in Bandung City - Wiguna, Willy; Muhtar, Entang Adhy; Ismanto, Slamet Usman (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2025)
This study examines the performance of the Civil Servant Police Unit (Satpol PP) in Bandung City in controlling street vendors (PKL). The issue focuses on the high rate of public order violations by PKL despite existing regulations. This qualitative descriptive research utilized in-depth interviews for data collection. The findings reveal that the effectiveness of Satpol PP's performance can be assessed through three approaches: goal-oriented, resource-based, and stakeholder-focused. The goal-oriented approach indicates the achievement of a Public Order Index of 6.90 in 2024, aligning with the vision of a livable city. The resource-based approach highlights the efficient management of funding, amounting to IDR 28.8 billion, and human resources predominantly from Grade II. Meanwhile, a public perception survey rated the performance as